Botanical composition of grassland according to the amount of Prosopis juliflora (Sw.) DC. trees in Carrizal-Chone, Ecuador - Roca, J. A.; Zamora, Maryury; Zamora, Yesenia; Félix, Miryam (Cuban Journal of Agricultural Science, 2020)
The effect of the amount of Prosopis juliflora (Sw.) DC. trees was evaluated in the botanical composition of the grassland in a cattle system of Carrizal-Chone region, Ecuador. Three tree amounts were used as treatments: low (1-4 trees/ha), medium (5-8 trees/ha) and high (9-12 trees/ha), distributed in a completely randomized design. A covariance analysis was applied to the variable final botanical composition (2014) in which the initial botanical composition (2012) was considered as covariate and tree amounts (3), species (5) and their interaction as the effects. A variance analysis was applied to the changes in the species coverage from 2012 to 2014, in which tree amounts (3), species (5) and their interaction were controlled. In both analyzes there was a highly significant effect (P˂0.001) of the interaction. The highest percentage of population was shown by the Megathyrsus maximus grass (saboya) at the high tree amount (45.7 %). In the latter (9-12 trees/ha), Megathyrsus maximus, Cynodon nlemfuensis and creeping legumes species predominated, to the detriment of other grasses and broadleaf plants. With the level 9-12 trees/ha, the greatest increases in the coverage of saboya species (5.1 %) and creeping legumes (2.2 %) were achieved. Other grasses and broadleaf plants reduced their cover in all treatments. It is concluded that with 9-12 trees/ha of Prosopis juliflora, the botanical composition of the grassland is improved, by increasing the coverage of the most important species in the cattle systems of Carrizal-Chone, Ecuador. Keywords: trees/ha, herbaceous cover, Megathyrsus maximus, silvopastoral